TINGKAT SPIRITUALITAS PESERTA DIDIK MADRASAH BERBASIS NONPESANTREN LEBIH TINGGI DARIPADA PESERTA DIDIK BERBASIS PESANTREN - Ummah, Siti Mahidlotul (al-Hikmah : Jurnal Studi Islam, 2020)
This study aims to determine differences in the level of spirituality of students in Islamic boarding schools and non-Islamic schools. Subjects were students in class X and XI at MA Darul Hikmah (pesantren-based madrasah) and MA Al-Musthofa (non-pesantren-based madrasah), data collection tools used were spirituality questionnaire, observation and documentation. The sampling technique in this research is Proportionate Stratified Random Sampling and the data analysis method used is the Independent Sample T-Test. The results of the comparison of the average value obtained is the average value of MA Darul Hikmah students by 161 and the average value of MA Al-Musthofa students by 165.5. This shows that the spirituality of pesantren-based madrasah students is lower than that of non-pesantren-based madrasah students. Then, the results of the T test show the t value of -1.4446821341 (t test<t table) and the significance value of the difference between MA Darul Hikmah and MA Al-Musthofa by 0.111 (Sig.>0.05), which means the difference between participants pesantren-based madrasah students with non-pesantren-based madrasah students are not significant. So it can be concluded that the level of spirituality of non-pesantren-based madrasah students is higher than the level of spirituality of pesantren-based students and the difference is not significant.